"Basement Boys" in the All-Gender Bathroom: Investigating Student-Inspired Trans-Activism and White Cisgenderist Barriers to Supporting Trans Students in School. Issue 8 (August 2022) - Omercajic, Kenan
Background/Context: The experiences of trans students in all-gender bathrooms are largely underexplored, as is the trans-activism by students to procure these spaces. Additionally, the role of teachers in supporting the creation of these spaces is largely absent from research regarding bathroom spaces. Purpose: This article elucidates the impact of student-inspired trans-activism that was mobilized through a gender studies educator in an urban school and her class project to foster trans inclusivity that resulted in the creation of two all-gender bathrooms. Participants: Four participants were involved in this study: a gender studies teacher, and her three students who either contributed to the creation of the all-gender bathrooms or actively used them following their implementation. Research Design: This qualitative paradigmatic case study took place at one high school (Capital High) and employs thematic and trans-informed theoretical analysis to semi-structured interviews to elucidate the potentialities and limitations of student-led trans-activism and the barriers to bathroom access. Findings: Emergent from this research is the significance of supportive educators and trans-inclusive education that collectively contribute to the overall trans-inclusive climate. However, pervasive white cistems exposed white male gender entitlement and the forces of cisgenderism at play in the school system, which amounted to the colonization of the all-gender bathrooms at Capital High by the "Basement Boys." Conclusion/Recommendations: The findings endorse the need to move beyond bathroom policy reform, and rely on a singular gender facilitative teacher to address the problem of cisgenderism. More gender-expansive commitments beyond one teacher's classroom are required, such as system-level directives that support integrating trans-affirmative education across the curriculum and resources to foster ongoing professional development in schools.